Internalisasi Nilai Ketauhidan melalui Pemahaman Sifat-Sifat Allah Swt: Kajian Konseptual dalam Pembelajaran Akidah Akhlak di Madrasah - Nurhalimah Nurhalimah; Mutiara Azzahra; Sindi Amelia; Ahmad Asrin (Prodi Pendidikan Keagamaan Islam, 2024)
This study aims to examine the process of internalizing the values of monotheism through understanding the attributes of Allah SWT in the learning of Aqidah Akhlak in madrasas. The phenomenon of weakening divine awareness and moral crisis among students shows that the learning of Aqidah Akhlak is still dominant in the cognitive aspect and has not touched the affective and spiritual realms. Therefore, an approach is needed that is able to instill the values of monotheism comprehensively through a correct understanding of the attributes of Allah SWT. This study uses a descriptive qualitative approach with a library research method. Data sources consist of primary literature in the form of the Qur'an, hadith, and classical aqidah books, as well as secondary sources from contemporary books and journals on Islamic education. Data analysis techniques are carried out using content analysis and conceptual interpretation to explore the relationship between theological concepts and the practice of values education. The results of the study indicate that understanding the obligatory, impossible, and jaiz attributes of Allah SWT plays a significant role in shaping students' awareness of monotheism. The process of internalizing monotheistic values occurs through three main stages: value transformation, value transaction, and value transinternalization. This study contributes to the development of an integrative, reflective, and contextual monotheistic-based Aqidah Akhlak learning model to address the challenges of modern Islamic education.